Breast Care Education for Post-Partum Mothers with Ineffective Breastfeeding Nursing Problems - Diani, Nanik Ratna (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
One of the problems that occurs after giving birth is a lack of knowledge about how to care for the breasts, resulting in a decrease in breast milk production. This scientific paper aims to provide breast care education for postpartum mothers with ineffective breastfeeding problems. Using a case study approach on two patients with ineffective breastfeeding problems at Poly GG Sam Husada Kediri on 15 until 17 March 2021. Data collection techniques include interviews, questionnaires, providing breast care education, and observation. Data analysis was carried out descriptively using the principles of nursing care management. Patients are given breast care education and evaluation for three days. Education was carried out for 3 days for client 1 and client 2, where on the first day the researcher provided education about breast care so that both clients understood how to carry out breast care correctly and appropriately. The researchers used the next 2 days to review the mother's knowledge of breast care and evaluate the mother's level of knowledge and ability to carry out breast care independently as well as the mother's ability to breastfeed effectively.